Case report: middle-aged woman from Ghana with unsteady gait and enlarging cerebellar mass. Issue 45 (November 2017) - Bajantri, Bharat; Venkatram, Sindhaghatta; Niazi, Masooma; Singh, Tushi; Diaz-Fuentes, Gilda
Abstract: Rationale: Neurosarcoidosis (NS) is an uncommon manifestation of systemic sarcoidosis, with a propensity for middle-agedwomen. Often discovered only at autopsy, rates of neurologic involvement (5%–10%) reported in the literature underscore a lack of sensitivity and specificity in current diagnostic methods. Patient concerns: Herein, we describe a 53-year-old woman who presented with gait imbalance and distal extremity muscular weakness. She was known to harbor a brain mass (4 years in duration) that was monitored and recently seemed to enlarge. Diagnosis: A subsequent brain biopsy showed necrotizing granulomatous inflammation suggestive of NS. However, no clinical or radiologic evidence of activity was found in other organs. Interventions and outcomes: Ultimately, endo and transbronchial biopsies were performed, providing histologic confirmation of systemic sarcoidosis. Lessons: This approach is advised in all instances of suspected NS where systemic involvement is in question.